RADIONUCLIDES BEHAVIOUR MODELLING OF 137CS AND 90SR IN GLYBOKE AND DALEKE LAKES OF CHERNOBYL EXCLUSION ZONE - Kutlakhmedov, Yuri; Iavniuk, Andrian (Proceedings of National Aviation University, 2013)
Results of 137Cs and 90Sr radionuclides behaviour modelling, which are the most spread radioisotopes in water bodies of Chernobyl Exclusion Zone are represented. Dynamics of radionuclides activity is modelled in water body components as the percentage of their total stock. Quantitative transfer of the radionuclides between water body components in the Chernobyl Exclusion Zone is determined and predicted.